Successful rehabilitation in conversion paralysis. Issue 6537 (28th June 1986) - Delargy, M A; Peatfield, R C; Burt, A A
Abstract : A rehabilitation programme for patients with conversion paralysis has been introduced in which they are offered physical rehabilitation. During an eight month period between October 1984 and May 1985 six patients who had been diagnosed as dependent on wheelchairs owing to conversion paralysis for a mean of 3 years (range 1-6 years) were entered into the inpatient neurorehabilitation programme. All six patients were able to walk within a mean of 41 days (range 10-70 days), and then relinquished a variety of aids and allowances as a result of their regained mobility. They continued to be independent at outpatient review for a mean of 10 months (range 8-15 months). Successful rehabilitation from wheelchair dependency can be achieved by a cost effective, prolonged, inpatient neurorehabilitation programme.